Gene Sequencing of Human Toxoplasma Gondii Isolated from Inoculated Sheep - Ola Kamal (Journal of Global Pharma Technology, 2018)
The persistence of nucleotides in precise order within a DNA structure is named DNA sequencing. In the medical diagnosis DNA Sequencing becomes a necessity in biotechnology. The technology of DNA sequencing is considered the most accurate method to complete genomes of many types and species, including the human, animals, plants, and microbial species. Studying new genes is significant in determining and identifying the drug target potential when it accompanied with phenotypes and diseases. Also evolutionary biology DNA sequencing to know how organisms are evolved and how they are differ. The inoculation of 17 samples of aborted females were the subject of the study using T.gondii tachyzoits isolation, it underwent gene sequence work from the period of the 15th September 2015 to 10th may 2016 .Genotyping using the Surface Antigen Glycoproteins (SAG2) gene locus refers to that isolates were (12 types II, 3 types I and 2 types III). All these types were illustrated by genetic map as homologues nucleotides sequencing.Keywords: DNA sequencing, Toxoplasma gondii, Sheep, Genotyping.